Wacana Tanding Stereotype Maskulinitas Pria Dalam Iklan Gillete Versi We Believe: The Best Men Can Be - Widiasari, Hairunnisa; Sugiarica Joni, I Dewa Ayu; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium; Vol 2 No 1 (2021): Jurnal Ilmu Komunikasi Vol 2 No 1 Tahun 2021, 2021)
Advertising has a great influence on the subconscious of the audience. Among the advertisements in the mass media, many advertisements related to male products are the accelerators that support male stereotypes of masculinity. Gillete’s advertisement is contrast to advertisements for male products which generally show toughness and bravery as elements of masculinity. The research aims to explain how the Discourse of Male Stereotype Masculinity in Gillete advertisement version We Believe: The Best Men Can Be uses a qualitative approach and is analyzed using Roland Barthes' Semiotic theory which consists of denotation, connotation and myth. The results showed that the advertisement contain a counter-discourse of male masculinity, in which Gillete presents the antithesis of masculinity in advertisements for male products in general. Like, men cry and express feelings, men are not interested in jokes related to sexual harassment and men can show their strength with attention rather than just physical use.   Keywords: Mass Media, Advertising, Masculinity, Semiotics